Design and fabrication of a device for measuring thermal diffusivity of food substances - Jamal, Parveen; Muhida, Riza; Raja, J.; Al-Herbawi, S. (2008)
Currently available various steady state and unsteady state (transient) methods for the measurement of thermal properties of food substances are limited and have several limitations. Modern research is in process of developing a device which is able to overcome these limitations. In this project a new device for measurement of thermal diffusivity was designed and fabricated. This device has several advantages over the available methods. Thermal diffusivity of apple, orange, papaya and potato was measured and found to 1.905 x 10-7 m2/s, 1.18 x 10-7 m2/s 2.12 x 10-7 m2/s and 2.205 x 10-7 m2/s respectively. The measured values were in good agreement with the values available in the literature. Empirical correlations using to correlate thermal diffusivity and temperature were developed for apples and potatoes. The effect of temperature on thermal diffusivity was studied by calculating the correlation coefficients.